Mitigating ice-induced offshore wind turbine vibrations utilizing a TMD system - Tan, Hong (author) (2017)
Offshore wind farms in Bohai Bay may be exposed to sea ice. The possible development of ice-induced vibrations can result in periodic high amplitude oscillations of the structure, which can significantly contribute to the fatigue of the structure. The main objective of this thesis is to investigate the mitigation effects of ice-induced vibrations by means of a tuned mass damper device. To achieve this goal, the ice-induced vibrations on the monopile type offshore wind structure has been analyzed numerically. On the basis of environmental data, the structure is first designed and numerically modeled. Then, an ice-crushing model has been implemented for the simulation of ice-induced vibrations on the monopile. It has been found that when the ice speed is intermediate, depends on different wind speeds, the frequency lock-in can be developed in both the first mode and second mode of the structure. The TMD model has been applied for investigating the mitigation effects. The model predicts that the TMD device can significantly mitigate the ice-induced vibration by absorbing the energy of the structure, and 1.5% tuned mass ratio is shown to be a suitable value for the investigated structure. Offshore and Dredging Engineering